2008
DOI: 10.1007/s11664-008-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Status of LWIR HgCdTe-on-Silicon FPA Technology

Abstract: The use of silicon as an alternative substrate to bulk CdZnTe for epitaxial growth of HgCdTe for infrared detector applications is attractive because of potential cost savings as a result of the large available sizes and the relatively low cost of silicon substrates. However, the potential benefits of silicon as a substrate have been difficult to realize because of the technical challenges of growing low-defect-density HgCdTe on silicon where the lattice mismatch is $19%. This is especially true for long-wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…equipment is being carried out for MCT MBE growth on large in diameter (up to 6") (112) Si substrates. It was shown that MCT/Si can be used for fabrication of high quality photonic IR FPAs in a spectral range up to 10 μm [6]. The MCT MBE growth on (013) GaAs substrates [7] have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…equipment is being carried out for MCT MBE growth on large in diameter (up to 6") (112) Si substrates. It was shown that MCT/Si can be used for fabrication of high quality photonic IR FPAs in a spectral range up to 10 μm [6]. The MCT MBE growth on (013) GaAs substrates [7] have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…While high resolution IR imaging can meet these challenges, there is a considerable cost in terms of power, form factor, and finance, in part due to higher costs of IR detector materials and material processing challenges when constructing small pitch FPAs. Despite recent advances, [8][9][10] copious research funds continue to be spent on developing larger format arrays with small pitch. CS addresses the question of whether it is necessary to physically produce smaller sensors in order to achieve higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, the goal of advancing this material technology to the long-wavelength (LWIR) regime has been hampered by the one to two orders of magnitude increase in dislocation density with respect to HgCdTe grown on lattice-matched bulk CdZnTe substrates. This deficiency in dislocation density has been shown to limit lifetimes, 9,10 lower mobility of carriers, 11 lead to larger dark currents in longwavelength detectors, 12,13 and ultimately reduce focal-plane array operability. 9,14 Current growth methods of HgCdTe/Si result in a dislocation density of mid 10 6 cm À2 to low 10 7 cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency in dislocation density has been shown to limit lifetimes, 9,10 lower mobility of carriers, 11 lead to larger dark currents in longwavelength detectors, 12,13 and ultimately reduce focal-plane array operability. 9,14 Current growth methods of HgCdTe/Si result in a dislocation density of mid 10 6 cm À2 to low 10 7 cm À2 . It has been the goal of the HgCdTe community in the past several years to reduce this value significantly.…”
Section: Introductionmentioning
confidence: 99%